IT HUB : CENTRALISED PLATFORM FOR IT FREELANCER - Shahrir, Luqman Roshdi (IRC, 2019)
This paper presents the importance of having a centralised platform to gather Information Technology (IT) professional or known as IT Freelancer that has technical skills in any IT related area to deliver services to customers by using mobile application as a medium of communication to acquire IT services. There are a few drawbacks in acquiring for IT services in the current world today. Lack of centralised platform that is focusing on delivering IT services has resulted in longer duration of time consumption and inefficient method in receiving IT services from IT Freelancer. The main objective of this research is to understand the business process of centralised platform in freelancing activities, develop a centralised mobile application for IT Freelancer and to evaluate the acceptance of the mobile application developed. In proving the importance of centralised platform , quantitative research has been conducted in analysing the need of mobile application in assisting IT Freelancer in delivering services. Agile methodology has been adopted in developing the mobile application as changes in requirement or its functionality can be implemented without affecting the development process. The prototype as mentioned has been developed for the usage of Android operating system by using Ionic Framework that blends in HTML, CSS and Typescript to produce the desired mobile application. Throughout the research and analysis being carried out, it has been proven that with the aid of IT Hub mobile application it simplifies the business process and easier for customer in receiving IT services. The benefit that can be gained through the mobile application for IT Freelancer to deliver their services is, it will reduce the time consumption for customer to acquire IT services and provide job for people with IT skills and knowledge.